2020
DOI: 10.1088/1755-1315/548/8/082033
|View full text |Cite
|
Sign up to set email alerts
|

Statistics of food quality as a factor in the dynamics of development of nutritionally dependent diseases in Russia

Abstract: The article presents the results of quality control of basic food products. The growth of nutritionally dependent diseases has been demonstrated. The absence of a direct relationship between the growth of nutritionally dependent diseases and the increase in the population older than working age has been established. The emerging tendency of an increase in the mortality rate of the able-bodied population due to nutritional diseases has been identified. Economic measures to improve the quality of food products a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…In the context of a global crisis and a global pandemic, only sustainable viable food systems will be able to withstand, which will not only maintain the achieved level of development, but also provide the population with stable earnings and sufficient food [10,11]. The pandemic has shown that the established food supply chains between countries are highly unstable, that it is necessary to have some reserve stocks in case of supply disruptions for countries that do not have sufficient production resources.…”
Section: Resultsmentioning
confidence: 99%
“…In the context of a global crisis and a global pandemic, only sustainable viable food systems will be able to withstand, which will not only maintain the achieved level of development, but also provide the population with stable earnings and sufficient food [10,11]. The pandemic has shown that the established food supply chains between countries are highly unstable, that it is necessary to have some reserve stocks in case of supply disruptions for countries that do not have sufficient production resources.…”
Section: Resultsmentioning
confidence: 99%
“…Maximum greening of the production complex and environmental friendliness of products will be the main competitive advantages of goods in the world market. Therefore, many commodity producers are already seeking to modernize their own production in accordance with green standards as much as possible [13].…”
Section: Resultsmentioning
confidence: 99%
“…The studies were carried out on 2 groups of calves with 10 heads in each live weight at the beginning of the experiment 104.7-106.1 kg for 90 days, taking into account the requirements of methodological recommendations for conducting zootechnical experiments [11] according to the scheme presented in Table 1. All the experimental livestock were in the same conditions: feeding was carried out twice a day, drinking from carpools, maintenance was loose.…”
Section: Materials and Methods Of Researchmentioning
confidence: 99%
“…In the post-dairy period, the young are transferred to vegetable feed. The main tasks of this period are: the formation of animals of the desired type; achieving high live weight and fatness during slaughter when growing for meat [11,12]. During this period, different feeding systems can be used: the same type of feeding throughout the year, when animals are given a balanced monofeed consisting of crushed and mixed feeds of different types in specified proportions, or seasonal feeding with a set of appropriate feeds.…”
Section: Introductionmentioning
confidence: 99%